Inner magnetic shielding material and method for production thereof - YAMANAKA YOSHIKAZU; TSUNEMATSU SHOUICHI; MATSUO SACHIO (2004)
An inner magnetic shielding material, characterized as comprising a cold rolled steel sheet having a surface roughness of 0.2 to 3 mumRa and, formed at least one surface thereof,, an organic resin coating film comprising C and H, or C, H and O, or C, H, O and N and having a thickness of 0.3 to 5 mum; and a method for producing the inner magnetic shielding material which comprises a step of annealing a cold rolled steel sheet, a step of adjusting a surface roughness of the annealed steel sheet to value of 0.2 to 3 mumRa, a step of forming an organic resin coating film comprising C and H, or C,H and O, or C, H, O and N and having a thickness of 0.3 to 5mum at least one surface of the cold rolled steel sheet. The inner magnetic shielding material has good resistance to rust and good degreasing and cleaning properties, is free from the danger of generating a corrosive gas, and also has good press formability. 本发明提供一种用于内磁屏蔽罩的材料，该材料具有防锈性能、良好的除油和冲刷性能、没有产生腐蚀性气体的危险，还具有良好的压力加工性。该材料在表面粗糙度为0.2-3μm Ra的冷轧钢板的至少一个表面上有厚度为0.3-5μm的基本上由C和H，或由C、H和O，或由C、H、O和N组成的有机树脂的涂层膜。该材料可以通过下述步骤制成：将冷轧钢板退火的步骤，将退火冷轧钢板的表面粗糙度调节为0.2-3μm Ra的步骤和在冷轧钢板的至少一个表面上形成厚度为0.3-5μm的基本上由C和H，或由C、H和O，或由C、H、O和N组成的有机树脂涂层膜的步骤。